Portable Baby Incubator Based On Fuzzy Logic - Qory Hidayati; Nur Yanti; Nurwahidah Jamal; Mey Adisaputra (Universitas Islam Sultan Agung, 2020)
The Global Action Report on Preterm Birth (2012) The United Nations Agency says, 15 million babies are born prematurely every year worldwide. Among them, more than one million babies die from complications due to premature birth. In 2010, Indonesia ranked fifth in the world with the highest number of premature babies in the world. The high birth rate for premature babies and the limited ability of parents to access health facilities to care for premature babies. The baby incubator serves to maintain a stable internal temperature and humidity so that it can help babies born prematurely to survive. This study aims to design and implement portable baby incubator control using fuzzy logic which consists of two fuzzy modules: based on Temperature and humidity. This baby incubator control uses fuzzy logic designed so that the system can display information on the baby's incubator temperature and humidity conditions, the baby's weight and the baby's heart rate without opening the incubator. The temperature in the system to be designed ranges between 36 ℃ -37 ℃, and the humidity is between 40% RH-60% RH. This incubator has a measurement and regulation system using temperature and humidity, namely the DHT22 sensor, the AC Dimmer Module to control PWM (Pulse Width Modulation), the acuator in the form of AC 220V incandescent lamps with a power of 60W and Arduino uno as a controlling microcontroller and an artificial fuzzy logic system Sugeno control method with a setting point value of 37 ℃ to maintain the stability of the temperature in the incubator in accordance with what is needed by premature babies. With the setting point at 37 ℃ the temperature in the baby incubator will survive in the range 37 ℃ -38 ℃.